2012
DOI: 10.1007/s11145-012-9413-4
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional factors affecting motivation during learning in adult basic and secondary education programs

Abstract: Research indicates that about a quarter of adult students separate from formal adult basic and secondary education (ABE/ASE) programs before completing one educational level. This retrospective study explores individual dispositional factors that affect motivation during learning, particularly students’ goals, goal-directed thinking and action based on hope theory and attendance behaviors, and self-perceptions of competency based on affective domain attributions about external and internal obstacles to learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…In Florida, adult education programs provide instruction to support the earning of a High School Equivalency Diploma (GED). Some individuals are enrolled simply because they are required to attend classes, and other individuals are highly dedicated to continuing their education and enjoy engaging in classes (for a review of student motivations, see Greenberg et al, 2013; Mellard, Krieshok, Fall, & Woods, 2013; Tighe, Barnes, Connor, & Steadman, 2013).…”
mentioning
confidence: 99%
“…In Florida, adult education programs provide instruction to support the earning of a High School Equivalency Diploma (GED). Some individuals are enrolled simply because they are required to attend classes, and other individuals are highly dedicated to continuing their education and enjoy engaging in classes (for a review of student motivations, see Greenberg et al, 2013; Mellard, Krieshok, Fall, & Woods, 2013; Tighe, Barnes, Connor, & Steadman, 2013).…”
mentioning
confidence: 99%
“…The unit was typical for this class in its length and in focusing on an academic language skill. Because of ABE learners' barriers to persistence (Mellard et al, 2013), the data collection period was limited to 8 weeks to help guard against attrition.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The complexities ABE/ESOL learners bring to academic language learning are many, including a range of formal educational backgrounds and levels of English (Kruidenier, MacArthur, & Wrigley, 2010) and situational barriers to persistence (Mellard, Krieshok, Fall, & Woods, 2013). Additionally, academic language is a formidable skill for even the most well-resourced second-language learner in that it makes complex cognitive and linguistic demands (Cummins, 1979; Zwiers, 2008).…”
mentioning
confidence: 99%
“…With regard to skill improvement, outcomes in three of the studies were associated with differences in the initial reading skill level of older learners (Calhoon and Petscher, 2013;Greenberg et al, 2012;Scarborough et al, 2012). Additionally, two of the adults studies found differences associated in demographics characteristics of students who maintained enrollment and those who dropped out (Greenberg et al, 2012;Mellard et al, 2012).…”
mentioning
confidence: 96%